Special competitive training and the effect it inflicts on some offensive planning skills in football - Naji Ali (College of Physical Education and Sport Sciences, 2024)
The study aimed to become acquainted with the special training for striking and the effect it inflicts on some planning skills for The Force of Al-Jawiya  for men in football. The researcher used the training curriculum of the two experimental groups and the before and after control of the tests. The research sample consisted of 20 youth players who were divided into two groups equally. The researcher used a set of personal interviews, test, measurements and information and data collection. The statistical data were processed by the following mathematical means, the standard deviation, tests (t) of the associated samples, and the test (T) of the independent samples, and the conclusions were. the competitive exercises that were applied had a positive room in developing accuracy and time, competing for offensive planning skills. The overlap of basic skills and physical qualities when the planning skills lent to an increase in the ability of the player when preforming the overall plan. The recommendations were to choose more realistic and more capable exercises to respond to similar play condition to its requirements. The need to use different methods and diversify different planning performance, trainings and not rely on one style.